Sexual and gender minority identity in undergraduate medical education: Impact on experience and career trajectory - Josef Madrigal (Public Library of Science (PLoS), 2021)
Introduction The wellbeing of sexual and gender minority (SGM) medical students and the impact of their experiences on career trajectory remain poorly understood. The present study aimed to characterize the incidence of mistreatment in SGM trainees as well as general perspectives on the acceptance of SGM individuals across medical and surgical specialties. Methods This was a cross sectional survey study of all actively enrolled medical students within the six University of California campuses conducted in March 2021. An online, survey tool captured incidence of bullying, discrimination, and suicidal ideation as well as perceived acceptance of SGM identities across specialties measured by slider scale. Differences between SGM and non-SGM respondents were assessed with two-tailed and chi-square tests. Qualitative responses were evaluated utilizing a multi-stage, cutting-and-sorting technique. Results Of approximately 3,205 students eligible for participation, 383 submitted completed surveys, representing a response rate of 12.0%. Of these respondents, 26.9% (n = 103) identified as a sexual or gender minority. Overall, SGM trainees reported higher slider scale scores when asked about being bullied by other students (20.0 vs. 13.9, P = 0.012) and contemplating suicide (14.8 vs. 8.8, P = 0.005). Compared to all other specialties, general surgery and surgical subspecialties had the lowest mean slider scale score (52.8) in perceived acceptance of SGM identities (All P < 0.001). In qualitative responses, students frequently cited lack of diversity as contributing to this perception. Additionally, 67.0% of SGM students had concerns that disclosure of identity would affect their future career with 18.5% planning to not disclose during the residency application process. Conclusions Overall, SGM respondents reported higher incidences of bullying and suicidal ideation as well as increased self-censorship stemming from concerns regarding career advancement, most prominently in surgery. To address such barriers, institutions must actively promote diversity in sexual preference and gender identity regardless of specialty.